Diabetic Foot Ulcer Complicated with Fracture and Osteomyelitis: X-ray Findings - Joseph Christian Tjahjadi; Annisa Shania Setiawan; Grace Chillia Surya Dharma; Irma Devi Mulyati; Budi Anugrah; Nada Adhityas Dwiputri; Paula Tama Siagian; Mathias Rusli; Wawan Kustiawan (Rumah Sakit Unggul Karsa Medika, 2022)
Diabetic foot ulcer is one of the complications of patients who have diabetes mellitus which is not well controlled. It is resulted from poor glycemic control, underlying neuropathy, peripheral vascular disease, and poor foot care. It could lead to osteomyelitis of the foot and amputation of lower extremities. Detailed history taking should be done in order to get a holistic view of disease progression and risk factors. Clinical presentations such as the presence of callus, loss of hair, muscle atrophy, ulcer, paresthesia, hypo- or hyperesthesia, anhydrosis could be present. Ulcers are most common in the weight-bearing areas such as plantar metatarsal head, heel, tips of hammer toes, and other prominent areas. Radiological investigations including plain x-rays should be done in order to look for any underlying osteomyelitis, the presence of air in the subcutaneous tissue, any signs of underlying fractures, and presence of a foreign body. In this case study, we presented X-ray finding of a diabetic foot ulcer case that complicated with fracture and osteomyelitis.